Supply chain networks evolving model based on local economy regions. (2016) - Liu, Yong; Zhuang, Yongrui; Lu, Nan
The cooperation networks of local region supply chains are influenced by not only the distance between enterprises but also resource and competitiveness, so it is necessary to combine these factors into the model to describe actual supply chain networks. In this paper, a supply chain networks evolving model based on local area seeking and mutual selection is proposed and its properties were carefully studied. The proposed model consists of individual strength-driven preferential attachment for each node, as well as local distance-driven preferential attachment for specific range of the new node. Analytical predictions and numerical simulations were both executed in order to explore evolutions and distributions of network. The results indicated that the degree distribution of the proposed model exhibits a crossover from power-law to Poisson distribution. Furthermore, the calculation of small-world quotient illustrates that the introduced model displays small-world properties.